Patient satisfaction with health services in Bangladesh - Andaleeb, Syed Saad; Siddiqui, Nazlee; Khandakar, Shahjahan (© 2007 The Author, Oxford University Press in association with The London School of Hygiene and Tropical Medicine., 2016)
This article was published in the Health Policy and Planning [© The Author 2007 Published by Oxford University Press ] and the definite version is available at : http://doi.org/10.1093/heapol/czm017 The Journal's website is at: http://heapol.oxfordjournals.org/content/22/4/263